Fever-related arrhythmic events in the multicenter Survey on Arrhythmic Events in Brugada Syndrome - Michowitz, Yoav; Milman, Anat; Sarquella-Brugada, Georgia; Andorin, Antoine; Champagne, Jean; Postema, Pieter G; Casado-Arroyo, Ruben; Leshem, Eran; Juang, Jimmy J M; Giustetto, Carla; Tfelt-Hansen, Jacob; Wijeyeratne, Yanushi D; et al. (Heart rhythm, 2018)
The literature on fever-related arrhythmic events (AEs) in Brugada syndrome (BrS) is currently limited to few case reports and small series. The present study aimed to describe the characteristics of fever-related AE in a large cohort of patients with BrS. The Survey on Arrhythmic Events in Brugada Syndrome is a multicenter study on 678 patients with BrS with first AE documented at the time of aborted cardiac arrest (n = 426) or after prophylactic implantable cardioverter-defibrillator implantation (n = 252). In 35 of 588 patients (6%) with available information, the AE occurred during a febrile illness. Most of the 35 patients were male (80%), Caucasian (83%), and proband (70%). The mean age at the time of AE was 29 ± 24 years (range 0.3-76 years). Most patients (80%) presented with aborted cardiac arrest and 6 (17%) with arrhythmic storm. Family history of sudden death, history of syncope, and spontaneous type 1 Brugada electrocardiogram were noted in 17%, 40%, and 71% of patients, respectively. Ventricular fibrillation was induced at electrophysiology study in 9 of 19 patients (47%). An SCN5A mutation was found in 14 of 28 patients (50%). The highest proportion of fever-related AE was observed in the pediatric population (age <16 years), with a disproportionally higher event rate in the very young (age 0-5 years) (65%). Males were involved in all age groups and females only in the pediatric and elderly groups. Fever-related AE affected 17 Caucasians aged <24 years, but no Asians aged <24 years. The risk of fever-related AE in BrS markedly varies according to age group, sex, and ethnicity. Taking these factors into account could help the clinical management of patients with BrS with fever.